PELATIHAN MENULIS KREATIF BERMUATAN BUDI PEKERTI SISWA SEKOLAH DASAR 014673 MEKAR SARI - Nelly Manurung, Rusda Nita; Perangin-Angin, Ersa; Beru Ginting, Sri Dinanta; Tanjung, Wilda Nurfadila (Smart Education, 2025)
Abstract: Writing activities are an important aspect taught to students in elementary schools. Many students still lack the ability to write creatively. This community service activity aims to improve the ability to write creatively with moral education content in Elementary School 014673 Mekar Sari students through face-to-face training. The subjects of this community service were 43 elementary school students, consisting of 22 students in class V A and 21 students in class VB. The participatory method was used in this training to stimulate students to be active in practicing writing poetry, both in theory and practice. Three meetings were held for theory training, poetry writing practice and presenting it. Based on the results of the scoring of poetry writing skills in the post-test session, the classical ability in writing poetry was 83.26%, whereas in the pre-test stage it was 65.94%. The results showed that poetry writing training with moral education content was able to improve the ability of Elementary School 014673 Mekar Sari students in writing creative poetry. The improvement in the participants' poetry writing skills can be seen in all aspects of poetry writing, including theme and meaning, power of imagination, accuracy of diction, and message. Keyword: creative writing, poetry, containing moral values, students Abstrak: Kegiatan menulis merupakan aspek penting yang dibelajarkan kepada peserta didik di sekolah dasar. Masih banyak peserta didik yang kurang dalam kemampuan menulis secara kreatif. Kegiatan pengabdian ini bertujuan untuk meningkatkan kemampuan menulis kreatif bermuatan pendidikan budi pekerti pada siswa Sekolah Dasar 014673 Mekar Sari melalui pelatihan tatap muka. Subjek pengabdian ini adalah siswa-siswa sekolah dasar sebanyak 43 orang, terdiri atas siswa kelas V A berjumlah 22 siswa dan siswa kelas VB berjumlah 21 siswa. Metode partisipatif digunakan dalam pelatihan ini guna menstimulasi para siswa untuk aktif dalam berlatih menulis puisi baik teori dan praktik. Pertemuan dilakukan sebanyak tiga kali untuk pelatihan teori, praktik menulis puisi dan mempresentasikannya. Berdasarkan hasil penskoran kemampuan menulis puisi pada sesi posttes diperoleh kemampuan klasikal dalam menulis puisi sebesar 83,26% dimana pada tahap pretes adalah 65,94%. Hasil menunjukkan bahwa pelatihan menulis puisi bermuatan Pendidikan budi pekerti mampu meningkatkan kemampuan para Sekolah Dasar 014673 Mekar Sari dalam menulis kreatif jenis puisi. Peningkatan kemampuan menulis puisi pada peserta terlihat pada seluruh aspek menulis puisi, mencakup tema dan makna, kekuatan imajinasi, ketepatan diksi, dan amanat. Kata kunci: menulis kreatif, puisi, bermuatan budi pekerti, siswa